Changes in procyanidins and tannin concentration as affected by cocoa liquor roasting - Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
AbstractPratylenchus coffeae is a parasitic nematoda that infected the roots of some plants, one of them is coffee. The Infection of Pratylenchus coffeae cause root tissue damage that led to root lession and make root become rotten, it will interfere the ability of roots to absorb water and nutrients in the soil which resulted in the growth of plants. At the moment, control of Pratylenchus coffeae are following integrated pests management (IPM) program, which integrated between the use of coffee resistant clone and application of biological agents. Research on biological control was conducted more intensive, at the moment; due to it is friendlier save against environment and cheaper then using chemical nematicides. The research was conducted to know the effects of Micorrhiza Helper Bacteria (MHB),Pseudomonas diminuta and Bacillus subtilis in suppressing the population of P. coffeaeas well as their effect on growth of coffee seedling.  Coffee arabica (Coffea arabica L.) seedling one moth old were used in the experiment. The experiment prepared with eight treatments and five  replications, as follows: A (Pseudomonas diminuta with density of 108 cfu / ml), B (Pseudomonas diminuta with density of 2x108 cfu / ml), C (Bacillus subtilis with density of 108 cfu / ml ), D (Bacillus subtilis with density 2x108 cfu / ml), E (Carbofuran nematicide 5 g formulation / pot), F (Pseudomonas diminuta and Bacillus subtilis with each density of 108 cfu / ml), K- (Nematoda inoculation but without bacteria and nematicide), K+ (coffee seedling  without any additional treatment). The experiment was conducted for sixteen weeks or about four months. The results of the experiment showed that application of MHB could suppress population of P. coffeae and increase coffee seedling growth significantly. Inoculation of B. subtilis at 108 cfu per seedling suppressed significantly nematoda population of 71.3% compared with untreated seedling but inoculated with nematoda. It was not significant different with carbofuran treatment which could suppress nematoda population by 89.7%. The same result also occur on the treatment of P. diminuta at density level 2.108 cfu/seedling, which could suppress nematoda population by 64.2%. Seedling growth were treated with MHB also significantly increase compared with seedling without treatment and inoculation of nematodas, especially on the treatment of B.subtilis at density level 108 cfu and P.diminuta at density level of 108 cfu, with increasing level of 35.4% and 34.2 %, respectively.Keywords: MHB (Mycorrhiza Helper Bacteria), Arabica coffee (Coffea arabica L.),  Pratylenchus coffeae, Bacillus subtilis, Pseudomonas diminuta.